تكيف اختبار الرفاهية النفسية لـ رايف على تلاميذ المرحلة الثانوية مع دراسة الفروق الجنسية - موشموش,بدرالدين; صالحي,سعيدة (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت الدراسة الحالية إلى تكيف مقياس الرفاهية النفسية لـ رايف "Ryff" والمترجم من طرف الباحث (موشموش بدرالدين,2022) , مع الكشف عن مستوى الرفاهية النفسية و الفروق الجنسية في درجتها الكلية وأبعادها. ثم حساب موثوقية وفق منهجية تطبيق وإعادة تطبيق الاختبار , و تكونت عينة الدراسة من 150 تلميذا . سجلت قيمةICC بـ 0.98 أما SEM فقيمتها 1.69 و سجل MDC قيمة 4.68 أما MDC% فكانت 3.04% . توصل الباحث إلى تمتع التلاميذ السنة الثالثة ثانوي بمستوى عالي من الرفاهية النفسية وعدم وجود فروق جنسية في مستوى درجتها الكلية. وأيضا في بعدي تقبل الذات و العلاقات الايجابية مع الآخرين. كما سجل تمتع الذكور بمستوى عالي مقارنة بالإناث في بعدي الاستقلالية ونمو الشخصية و العكس في بعدي التمكن البيئي والهدف في الحياة. Abstract: The purpose of this study, was to adapt the Ryff psychological well-being scales, Translated by the researcher (mouchmouche Badreddine, 2022) and revealing the level of psychological well-being , and gender differences in their general notes and dimensions. The reliability of the scale was calculated according to the methodology test - retest ,the sample consisting of 150 students. The ICC value was recorded at 0.98 . the SEM value was 1.69 . the CDM recorded a value of 4.68 , and the CDM% was estimated at 3.04% . The researcher found that the third-year high school students had a high level of well-being , and that there was no gender differences in the level of their overall grades . Also in the dimension of self-acceptance and positive relationships with others . Boys have achieved a high level compared to girls in the dimensions of independence and personal growth, and vice versa in the dimensions of environmental autonomy and life purpose.
Keywords: الرفاهية النفسية; دراسة الموثوقية; Psychological well-being; validation studies; school students